Introduction to analytical chemistry - Summerfield, Stephen; Reid, Helen (The University of Hull)
A general introduction to analytical chemistry with a special focus upon the analytical process, quality assurance, and guidance on solution preparation including volumetric and concentration calculations. It also includes a bibliography of useful texts for the analytical chemist.